Residents' Appreciation of Cultural Heritage in Tourist Centres - A Micro-simulation Modelling Approach to Amsterdam - Eveline van Leeuwen; Karima Kourtit; Peter Nijkamp (Tinbergen Institute, 2013)
This paper addresses the question of the value attached by residents of tourist places to the wealth of cultural heritage in their city. Particular attention is given to the impact of various types of information (ranging from traditional to advanced ICT sources) on the residents' valuation of cultural heritage. Based on an extensive survey among inhabitants of Amsterdam, a two-stage analytical approach is adopted: (i) an econometric (ordered logit) modelling approach to identify the most prominent vectors of the residents' appreciation of cultural heritage; (ii) a micro-simulation modelling approach to generate a comprehensive picture of the value set of inhabitants regarding the cultural heritage in their city. This information may also serve as a basis for urban strategies on tourism policy, cultural heritage planning and information services management.
Keywords: L83; 330; Cultural Heritage; Residents; Tourism; Ordered Logit Model; Microsimulation; ICT; Amsterdam